Analisis Dampak Konseling SADARI terhadap Pengetahuan dan Kompetensi WUS dalam Deteksi Dini Kanker Payudara - Adista, Nuria Fitri; Apriyanti, Ika (Universitas Faletehan, 2024)
Breast-Self Examination (BSE) is an effective method for the early detection of breast cancer, potentially reducing mortality rates by 25-30%. Women with low knowledge about breast cancer and BSE need education starting from adolescence. This study aimed to measure and analyze changes in the ability of Women of Childbearing Age (WCA) to perform BSE before and after counseling in Pejaten Village, Kramatwatu, Serang, Banten. The method used was analytical survey. The results of the study showed a significant increase in WCA knowledge about BSE from 21% (good) in the pretest to 83% (good) in the posttest after counseling. Before the counseling, 98% of WCA were unable to perform BSE, but after it 95% were able to perform it. The Wilcoxon test showed a significance of 0.000 (p<0.05), indicating that the counseling had a significant impact on the knowledge and ability of WCA to perform BSE. Village, health workers, and the community were recommended to collaborate to regularly conduct counseling to improve understanding and skills in the early detection of breast cancer.